Diversity of leaf spot pathogen associated with vegetable from Chhatrapati Sambhajinagar, Maharashtra - Ghuge, Radha V.; Rathod, Sulochana R.; Zinjade, Ajay S. (Journal of Ecobiotechnology, 2025)
Vegetables are important constituents of Indian agriculture and nutritional security due to their short duration, high yield, nutritional richness, economic viability and ability to generate on-farm and off-farm employment. The fungal diseases are serious threats to vegetable crop production. The leaf spot infection can result in chlorosis, defoliation, and a decline in the photosynthetic capacity of plant, potentially reducing fruit yield by up to 100% loss. During this investigation the genetic diversity of leaf spot pathogen, the infected samples were collected from different localities of Chhatrapati Sambhajinagar in Kharif and Rabi season of 2023-2024. It was found that the five different leaf spot pathogens via; Cladosporium cladosporioides-1, Cladosporium cladosporioides-2, Curvularia crepinii, Curvularia geniculata and Macrophomina pseudophaseolina from different localities were shows the morphological as well as genetic diversity among each other. The genetic variability in the leaf spot pathogen isolates may be due to difference in geographical and environmental conditions. The ITS primer is used to analysis, it was found diversity among leaf spot pathogen isolates at molecular characterization. The phylogenetic analysis using ITS Primer showed the grouping of leaf spot pathogen isolates strictly according to their cultural characteristics and degree of pathogenicity and not the geographical origin.